Performance of a nonlinear hybrid base isolation system under the ground motions - Li, Chunxiang; Chang, Ke; Cao, Liyuan; Huang, Yu (Soil dynamics and earthquake engineering (1984), 2021)
In order to reduce the displacement demand of the isolation layer under strong earthquakes, especially strong near fault pulse-like ground motions, the base isolation system-tuned mass damper inerter (BIS-TMDI) system is explored taking the nonlinear hysteretic characteristics of the isolation layer into inclusion. Likewise, different from traditional layout of the BIS-TMDI systems, the TMD is placed on the superstructure (such as first floor or third floor, etc.) rather than on the isolation layer and linked to the ground by an inerter. By resorting to the equivalent linearization method (ELM) and genetic algorithm (GA) optimization, the optimal design method of nonlinear BIS-TMDI system is established and then, the performance of the system is numerically investigated. Results demonstrate that the nonlinear BIS-TMDI system can significantly reduce the displacement demand of the isolation layer, and its control effectiveness and stroke performance are better than those of the nonlinear BIS-TMD system. The influences of the parameters of the superstructure, isolation layer, and earthquake ground motions on the vibration mitigation is further scrutinized. It follows that the robustness of nonlinear BIS-TMDI system is much better than that of nonlinear BIS-TMD system. Analyzing the nonlinear BIS-TMDI system subjected to the near-fault pulse-like ground motions, the superiority of the system in reducing the displacement of isolation layer, the responses of superstructure and the stroke performance of TMDI are further verified. •An exploration is made on the nonlinear BIS-TMDI system different from its traditional layout.•Employing ELM and GA, the design method of nonlinear BIS-TMDI system is presented.•Reveal the parameter influence behaviors and conduct the time history analysis of nonlinear BIS-TMDI system.•The nonlinear BIS-TMDI system remarkably reduces the isolation layer displacement and has high overall performance.